2017
DOI: 10.1007/s00408-017-0012-7
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalization Among Patients with Sarcoidosis: A Population-Based Cohort Study 1987–2015

Abstract: Purpose There is little information about healthcare utilization for sarcoidosis. This study examined need for hospitalization as a measure of healthcare burden in this disease. Methods A cohort of Olmsted County, Minnesota residents diagnosed with sarcoidosis between January 1, 1976 and December 31, 2013 was identified using the resources of the Rochester Epidemiology Project. Diagnosis was made based on individual medical record review. For each sarcoidosis subject, one sex and age-matched comparator witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 16 publications
1
8
0
2
Order By: Relevance
“…These studies have examined multimorbidity, 27,31 infection, 28,32 malignancy, 33,34 cardiovascular disease, 29 venous thromboembolism, 35,36 fractures, 37,38 and autoimmune diseases. 7 Patients with sarcoidosis are hospitalized more often than individuals without sarcoidosis 39 and in-hospital mortality is higher. 40 Overall, these data underscore the burden of sarcoidosis in terms of premature mortality and comorbidity.…”
Section: Mortalitymentioning
confidence: 99%
“…These studies have examined multimorbidity, 27,31 infection, 28,32 malignancy, 33,34 cardiovascular disease, 29 venous thromboembolism, 35,36 fractures, 37,38 and autoimmune diseases. 7 Patients with sarcoidosis are hospitalized more often than individuals without sarcoidosis 39 and in-hospital mortality is higher. 40 Overall, these data underscore the burden of sarcoidosis in terms of premature mortality and comorbidity.…”
Section: Mortalitymentioning
confidence: 99%
“…Research studies predict that the number of hospital admissions in patients with sarcoidosis is higher than those without it [7]. Therefore, the disease poses a significant financial burden on the United States healthcare industry.…”
Section: Discussionmentioning
confidence: 99%
“…In an international population of Australian SSc patients, an average of 2.8 annual hospitalizations per patient without ILD and 3.9 annually per SSc patient with ILD were reported (9). Additionally, prior research has shown that hospitalization occurs more frequently in patients with other rheumatologic conditions than the general population, including in giant cell arteritis (13), and sarcoidosis (14).…”
Section: Discussionmentioning
confidence: 99%